PENERAPAN PEMBERKASAN MENGGUNAKAN APLIKASI BANK INDONESIA RECORDS MANAGEMENT SYSTEM (BI-RMS) PADA DIVISI ARSIP BANK INDONESIA - Fauziah, Neneng; Rohmawati, Lia (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2021)
This observation aims to find out how process Application of Filling Using the Application Bank Indonesia Records Management System (BI-RMS) on Divisi Arsip Bank Indonesia. The background to problem that prompted the author to make observations about filling was considering the use value and function of archives that are so important for organizing life so the need for good archive management by following the dynamics of technological developments that occur in the community. From observation made in Divisi Arsip Bank Indonesia archive management activities including the filling activities, have taken advantage of technology. As a tool for processing, accessing and disseminating and preserving archives. Application of Filling Using the Application Bank Indonesia Records Management System consists of file collection activities, rapid, input and validation, printing of label and list of file contents. And file storage in storage media.